2017
DOI: 10.5194/acp-2017-648
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nitrous acid formation in a snow-free wintertime polluted rural area

Abstract: Abstract.Nitrous acid (HONO) photolysis is an important source of hydroxyl radicals (OH) in the lower atmosphere, in particular in winter when other OH sources are less efficient. The nighttime formation of HONO and its photolysis in the early morning have long been recognized as an important contributor to the OH budget in polluted environments. Over the past few decades it has become clear that the formation of HONO during the day is an even larger contributor to the OH budget, and additionally 5 provides a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 56 publications
(87 reference statements)
4
3
0
Order By: Relevance
“…Equation (7) does not include a chemistry-transport model nor accounts for the existence of a vertical profile of concentrations, which may bias the calculation on HONO source strength. However, the method for predicting the ground source using homogeneous mixed air columns is consistent with other recent studies (Stemmler et al, 2006;Tsai et al, 2017). Tsai et al (2017) clearly showed the presence of an important ground source of daytime HONO at a rural basin in Utah during winter (no snow, low temperatures).…”
Section: Comparison Of Soil Emissions and Observed Missing Sourcesupporting
confidence: 75%
See 4 more Smart Citations
“…Equation (7) does not include a chemistry-transport model nor accounts for the existence of a vertical profile of concentrations, which may bias the calculation on HONO source strength. However, the method for predicting the ground source using homogeneous mixed air columns is consistent with other recent studies (Stemmler et al, 2006;Tsai et al, 2017). Tsai et al (2017) clearly showed the presence of an important ground source of daytime HONO at a rural basin in Utah during winter (no snow, low temperatures).…”
Section: Comparison Of Soil Emissions and Observed Missing Sourcesupporting
confidence: 75%
“…However, the method for predicting the ground source using homogeneous mixed air columns is consistent with other recent studies (Stemmler et al, 2006;Tsai et al, 2017). Tsai et al (2017) clearly showed the presence of an important ground source of daytime HONO at a rural basin in Utah during winter (no snow, low temperatures). They inferred that ground surface fluxes may account for 63 ± 32 % of the unidentified HONO daytime source throughout the day.…”
Section: Comparison Of Soil Emissions and Observed Missing Sourcesupporting
confidence: 75%
See 3 more Smart Citations